REGULARITY CODITIONS IN NONLINEAR PROGRAMMING PROBLEMS - L. I. Minchenko; A. E. Leschov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Weak regularity conditions are studied. Necessary and sufficient conditions of R -regularity are obtained. The relations between different types of regularity conditions are investigated.